Extraction Metallurgy Of Copper From Chalcopyrite Concentrates Without Sulfuric Acid Generation Via Chlorination-Gaseous Chlorination Of Sulfide Concentrates - T. Tamagawa (Society for Mining, Metallurgy & Exploration, 1999)
A gaseous chlorination process for hydrometallurgical treatment of a chalcopyrite concentrate was investigated. The overall process is visualized to consist of low temperature chlorination-selective oxidation, followed by aqueous chloride leaching and SX-EW for producing electrolytic copper elemental sulfur and ferric oxide. In this article, the chlorination phase of the processes is described. Initially, the chlorination behavior of chalcopyrite-concentrate micro-pellets was investigated using a small batch-type fluidized bed reactor. The optimum conditions thereby established was used in continuous chlorination tests. The chlorinated products thus prepared were used in the selective oxidation phase of the investigation.